2016
DOI: 10.1161/circgenetics.115.001271
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Scores Predict Recurrence of Acute Coronary Syndrome

Abstract: Background— Several clinical risk estimation tools have established their role in the prediction of recurrence of acute coronary syndrome (ACS), but the value of genetic risk scores (GRSs) remains unclear. We examined how well 2 different GRSs estimate recurrent ACS and whether clinical factors are associated with GRSs. Methods and Results— A cohort of 2090 consecutive patients with ACS who underwent coronary angiography between July 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Combined into genetic risk scores (GRS), these SNPs predict adverse cardiovascular events in various populations with and without prior cardiovascular disease [710]. Although the majority of loci identified seem to act through induction of atherosclerosis, little is known about the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Combined into genetic risk scores (GRS), these SNPs predict adverse cardiovascular events in various populations with and without prior cardiovascular disease [710]. Although the majority of loci identified seem to act through induction of atherosclerosis, little is known about the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…For GRS-47, a significant association with ACS recurrence was confirmed regardless of clinical factors (HR = 1.17, 95% CI: 1.01-1.36, p = 0.037). For GRS-153, the association with relapses of ACS and/or mortality was not confirmed; however, an association of GRS-32 with a three-vessel lesion was found, and, for GRS-47, an inverse correlation with smoking and MI featuring ST elevation was revealed [53].…”
Section: Modern Models Of Genetic Risk Calculators (2016-2020)mentioning
confidence: 85%
“…Thus, most authors have reported an improvement in prognostic power when a GRS is added to existing CVD risk calculators; however, some authors have not confirmed (partially or completely) the association between a GRS and CVDs [5,32,39,41,42,53,77]. This lack of associations can be explained by the need for a more thorough functional analysis of the SNPs included in GRSs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations